Solid Waste Treatment Using Multi-Criteria Decision Support Methods Case Study Lattakia City - Raed Jafar; Zahraa Alhindawee; Haytham Shahin; Adel Awad (مجلة بغداد للعلوم, 2023)
Lattakia city faces many problems related to the mismanagement of solid waste, as the disposal process is limited to the random Al-Bassa landfill without treatment. Therefore, solid waste management poses a special challenge to decision-makers by choosing the appropriate tool that supports strategic decisions in choosing municipal solid waste treatment methods and evaluating their management systems. As the human is primarily responsible for the formation of waste, this study aims to measure the degree of environmental awareness in the Lattakia Governorate from the point of view of the research sample members and to discuss the effect of the studied variables (place of residence, educational level, gender, age, and professional status) on the level of environmental awareness. Data were collected and analyzed using the SPSS.21 statistical package. This study also presents a methodology to find the optimal scenario for solid waste treatment using the hierarchical analysis method represented by Expert Choice 11.1.